Cumulative Repetition Effects Across Multiple Readings of a Word: Evidence From Eye Movements. Issue 3 (3rd April 2018) - Kamienkowski, Juan E.; Carbajal, M. Julia; Bianchi, Bruno; Sigman, Mariano; Shalom, Diego E.
Abstract : When a word is read more than once, reading time generally decreases in the successive occurrences. This Repetition Effect has been used to study word encoding and memory processes in a variety of experimental measures. We studied naturally occurring repetitions of words within normal texts (stories of around 3, 000 words). Using linear mixed models to analyze the evolution of fixations over successive repetitions, we observed an interaction between corpus word frequency and repetition. Specifically, we found a decrease in fixation durations in words with low frequency but not with high frequency, and both values converged after five or six repetitions. Furthermore, we showed that repetition of a lemma is not enough to evoke this effect. Our results are in agreement with predictions formulated by the context-dependent representation model, and this adds new arguments to the discussion of the sources of the repetition effect.